Functional hyaluronate collagen scaffolds induce NSCs differentiation into functional neurons in repairing the traumatic brain injury. (November 2016) - Duan, Hongmei; Li, Xiaoguang; Wang, Cong; Hao, Peng; Song, Wei; Li, Manli; Zhao, Wen; Gao, Yudan; Yang, Zhaoyang
Graphical abstract: Abstract: The traumatic brain injury (TBI) usually causes brain tissue defects, including neuronal death or loss, which ultimately results in dysfunction in some degree. The cell replacement therapy is now one of the most promising methods for such injury. There are currently various methods to induce the differentiation of stem cells into neurons, but all extremely complex, slow and unstable. Here we report that the sodium hyaluronate collagen scaffold loaded with bFGF (bFGF-controlled releasing system, bFGF-CRS) can induce neural stem cells (NSCs) to differentiate into multi-type and mature functional neurons at a high percentage of 82 ± 1.528% in two weeks. The quantitative real-time (QRT) PCR results reveal that a long-term activation of bFGF receptors could up-regulate ERK/MAPK signal pathways, thus facilitating the formation of presynaptic and postsynaptic structure among the induced neuronal cells (iN cells). The functional synaptic connections established among iN cells were detected by the planar multielectrode dish system. When jointly transplanting the bFGF-CRS and NSCs into the CA1 zone of the rat TBI area, the results suggested that bFGF-CRS provided an optimal microenvironment, which promoted survival, neuronal differentiation of transplanted NSCs and functional synapse formation not only among iN cells but also between iN cells and the host brain tissue in TBI rats, consequently leading to the cognitive function recovery of TBI rats. These findings in vitro and in vivo may lay a foundation for the application of bFGF-CRS and shed light on the delivery of exogenous cells or nutrients to the CNS injury or disease area. Statement of Significance: A sodium hyaluronate collagen scaffold was specifically functionalized with nutrient-bFGF which can induce the differentiation of neural stem cells (NSCs) into multi-type and mature functional neurons at a high percentage in two week. When jointly transplanting the bFGF-CRS and NSCs into the CA1 zone of the traumatic brain injured area of adult rats, the bFGF-CRS could provide an optimal microenvironment, which promoted survival, migration and neuronal differentiation of transplanted NSCs and functional synapse formation among iN cells, as well as between iN cells and host brain tissue in TBI rats, consequently leading to the cognitive function recovery of TBI rats.